The Relationship between Organizational Agility and Organizational Health in Hospitals Affiliated to Shahid Beheshti University of Medical Sciences - Khalil Ali Mohamadzadeh; Amene Darabi; Mehrnoosh Jafari (Tehran University of Medical Sciences, 2017)
Background and Aim: Organizational agility is regarded an important factor for hospital effectiveness. Considering the necessity of hospital effectiveness, focus on organizational health can ensure the future success of an organization. This study mainly aims to determine the relationship between organizational agility and organizational health in hospitals affiliated to Shahid Beheshti University of Medical Sciences (SBMU). Materials and Methods: This is an applied, descriptive-correlational research. The population of the study included all SBMU hospital employees. The 375 members of the sample were selected based on Morgan and Krejcie table. The sampling method was multistage. Data collection tool was the questionnaires of organizational agility and organizational health. The questionnaires were valid based on the expert's judgment, and Cronbachchr('39')s alpha reliability value of the questionnaires was 0.88. The data were analyzed by descriptive and inferential statistics (Pearson correlation, regression, and t-test), using SPSS software. Results: The correlation between organizational agility and organizational health was positive and significant (r=0.66, P<0.05). A significant difference was observed between mean organizational agility and mean reference (-0.43, P<0.05) and also between mean organizational health and mean reference (-0.55, P<0.05). Conclusion: Hospital managers need to work hard to promote organizational agility so that in addition to obtaining competitive advantage, they can improve organizational health by giving an appropriate and timely response to changes and taking advantage of the obtained opportunities.